Small samples, big problems—the inability to provide a sample in breath alcohol testing: Case reports - Aaron Olson (Forensic Science International: Synergy)
Breath alcohol testing is a cornerstone of impaired driving investigations, yet some individuals are physiologically unable to provide adequate breath samples, leading to charges of refusal despite efforts to comply. This paper presents seven case reports of individuals who failed to meet the minimum volume requirements of the DataMaster DMT breath alcohol analyzer due to factors such as age, gender, respiratory conditions, and smoking history. Despite seemingly genuine attempts to provide valid samples, these individuals were charged with refusing to submit to a chemical test.The case reports in this paper highlight the vulnerabilities in current testing protocols, including the one-size-fits-all volume requirement, equipment problems, measurement uncertainty, individual anxiety, operator bias, and lack of transparency. Proposed improvements include alternative testing methods (e.g., blood or urine), individualized volume requirements, enhanced operator training, slope-based sampling, changes in equipment design, regular volume calibration, mandatory data collection, and independent scientific review.